Smart Transportation System Evolution: a Comprehensive Mapping and Analysis - Younus, Muhammad; Nurmandi, Achmad; Rohrohmana, Nurainni (Journal of World Science, 2023)
Smart transportation is an important trend worldwide, reducing accidents, traffic jams, and pollution. It uses technology and communication to parse errors and monitor everything online. This research aims to determine how to implement a smart transportation system to provide convenience for users and the city. Smart transportation systems are designed to reduce accidents, pollution, and other problems. However, many cities still need to implement them and require government approval. This research aims to implement the system in every city to ensure citizens can use it more. This research uses a qualitative and bibliometric analysis approach to analyze bibliographic research data in journals from 2012 to 2022. The cluster obtained from software shows that smart transportation uses the most electricity from ordinary transportation and requires a ready implementation system. Other topics related to implementing an intelligent transportation system, such as benefits and how to implement it, are obtained. The conclusion is that smart transportation must be implemented to reduce risks and make urban citizens feel more secure and comfortable using it.